Growth and prolificacy performance of Garole sheep raised under semi-arid conditions - PRAKASH, VED; PRINCE, L L L; SHARMA, R C; KUMAR, ARUN (The Indian Journal of Animal Sciences, 2017)
The growth and prolificacy performance of Garole sheep reared under semi-arid conditions at ICAR-Central Sheep and Wool Research Institute, Avikanagar, Rajasthan was evaluated in the present study. The body weight records of 1,058 lambs and prolificacy records of 624 ewes collected over a period of 19 years (1997-2015) were analyzed. The overall least squares mean for body weights at birth (BWT), 3 month (3WT), 6 month (6WT), 9 month (9WT), 12 month (12WT), pre-weaning (0-3 month) average daily gain (ADG1) and post weaning (3-6 month) average daily gain (ADG2) were 1.18±0.02 kg, 6.42±0.12 kg, 9.87±0.18 kg, 11.77±0.25 kg, 13.74±0.32 kg, 56.87±1.22 g and 40.19±1.39 g, respectively. The effect of sex of lamb, period of birth and dam weight at lambing were significant for all growth traits. Significant variation in growth performance, multiple birth and litter size was observed over the period. The body weight and average daily gain of Garole sheep improved over the years. In last 15 years, improvement ranging from 19.56 to 29.51% was observed for various growth traits studied. The multiple births in Garole ewes were 58.01% with a litter size of 1.68 at birth. The prolificacy and litter size in semi-arid conditions were similar to the native tract especially in initial period. Period of lambing and weight of dam at lambing significantly affected litter size at birth. Results showed that Garole performed well in the semiarid conditions and can be successfully reared in these conditions with updated management.